Introduction to Architecture Studio: Geometry, Rules and Patterns - Colakoglu, Birgul (ECAADE-EDUCATION & RESEARCH COMPUTER AIDED ARCHITECTURAL DESIGN EUROPE, 2011)
Introduction to architecture studio introduces students of architecture with fundamentals of design and design thinking. Here, the students learn: analytical thinking by constructive analysis of precedents; language of design by using basic geometric elements and operational/transformational principles among them; and principles of form making by engaging in constructing the form. The paper explains the process of the studio in which shape grammar methodology is utilized in teaching analytical thinking, language of design and principles of form making to architecture students.
Keywords: Architecture Studio Education; Shape Grammars; Rule Based Design; Architecture